ACT math for dummies - Zegarelli, Mark. (Hoboken, NJ : Wiley, 2011)
Provides an easy-to-follow study guide for the ACT math test, complete with practice problems and strategies to help you prepare for exam day -
Getting into the act: an overview of ACT math basics -- Building your pre-algebra and elementary algebra skills -- Digging in to intermediate algebra and coordinate geometry -- Visualizing plane geometry and trigonometry -- Tracking your progress with practice tests -- The part of tens.
Includes index.
Keywords: ACT Assessment -- Study guides; Mathematics -- Problems, exercises, etc; Mathematics -- Examinations -- Study guides; Mathematics -- Examinations, questions, etc; ACT Assessment -- Study guides; Mathematics -- Problems, exercises, etc; Mathematics -- Examinations -- Study guides